Potential and prospects of value chain development for fruits and vegetables in India - SHRUTI, SHRUTI; SHARMA, J P; GILLS, RESHMA (The Indian Journal of Agricultural Sciences, 2019)
Globally, India is second largest producer of horticultural produce, however, the postharvest loss estimated to be high (30-40%) and the insignificant proportion of vegetable (2%) and fruit (4%) produce are being processed. Therefore, for increasing the farmers’ income, the need of the hour is to focus on beyond farm production, developing farmers’ capacity for processing and linking them with market and other supporting institutions to promote efficient value chain. However, the value chain in fruits and vegetable is complex due to its perishability, high fluctuations in demand and prices and dependence on climate conditions. Hence, the need to stress on commodity and community based processing centres, developing partnership between local processors and marketing institutions, improving competency of development officers and infrastructure development for efficient value chain promotion. The paper attempt to document the need and potential of value addition; status of actors, activities and strategic network of value chain in present scenario, the challenges of value chain at recent and strategies to improve it.